Navigating communication barriers: The role of family dynamics in deaf adolescents' social interaction - El-Fikri, Dewi Nabela Sofya; Maulina, Apriya Sani; Asri, Adinda Ratu Kencana; Masfia, Irma; Fahmi, Zulfa (Journal of Advanced Guidance and Counseling, 2024)
Purpose - This study aims to understand the level of interaction and implementation of parenting patterns that can affect the lives of deaf teenagers. Method - In this study, the researcher uses a qualitative method with a case study and exploratory-descriptive approach. The research was conducted from February-April 2024. Data collection techniques include interviews, observations, and documentation. The analysis techniques consist of data collection, data reduction, data presentation, and drawing conclusions. Result - This study highlights the importance of social interaction and parenting patterns for deaf teenagers. It was found that awareness of the subject's condition begins from birth, with the main challenges in communication and environment. Parents tend to apply authoritative and democratic parenting styles. Communication with other deaf individuals uses sign language, while communication with family members or individuals without special needs uses spoken language. The subject's skills such as sewing, pantomiming, and painting can boost their self-confidence and enhance their social interaction skills by participating in competitions related to their skills. Originality - This research reinforces the findings on social interaction of deaf teenagers with individuals without special needs, as well as the independent parenting patterns applied by parents to deaf teenagers with special needs.***Tujuan - Penelitian ini bertujuan untuk memahami tingkat interaksi serta implementasi pola asuh orangtua yang dapat mempengaruhi kehidupan remaja tunarungu. Metode - Dalam penelitian ini peneliti menggunakan metode kualitatif dengan studi kasus dan eksploratif-deskriptif. Penelitian ini dilakukan dari Februari-April 2024. Teknik pengumpulan data dalam penelitian ini adalah wawancara, observasi dan dokumentasi. Teknik analisis dalam penelitian ini terdiri dari pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan.Hasil penelitian - Penelitian ini menyoroti pentingnya interaksi sosial dan pola asuh bagi remaja tunarungu. Ditemukan bahwa kesadaran akan kondisi subjek dimulai sejak kelahiran, dengan tantangan utama dalam komunikasi dan lingkungan. Orang tua lebih menerapkan pola asuh otoriter dan demokratis. Cara komunikasi terhadap sesama berkebutuhan khusus tunarungu menggunakan bahasa isyarat sedangkan terhadap keluarga ataupun orang yang tidak memiliki kebutuhan khusus tunarungu menggunakan bahasa bibir. Adanya keterampilan yang dimiliki subjek seperti menjahit, pantomime, dan melukis yang dapat meningkatkan kepercayaan dirinya serta kelancaran dalam berinteraksi sosial dengan mengikuti ajang perlombaan sesuai dengan keterampilan yang dimilikinya. Originalitas– Penelitian ini memperkuat penemuan mengenai interaksi sosial remaja tunarungu terhadap individu yang tidak memiliki kebutuhan khusus, serta pola asuh mandiri yang di terapkan orangtua terhadap remaja yang memiliki kebutuhan khusus tunarungu.